(3QhVI GdYbdGAs - (3eMeO Hf MHGf Hf CMeO Hf MHGf Hf eYGP Hf eYHO GdJejej, CHh MGJe GdHSJj, hjbGd dg GHf MHGf,J (B354 (3g` s ((3MQGf s)
(3ChdgG (B:s
(3GdMeO ddg GdPi Ndb GdEfSGf ef fWaI Ke ef YdbI Ke ef eVZI eNdbI hZjQ eNdbI s
(3BNQgG (B:s
(3LYdfG Gddg aef OYJg JHGTjQ GdJhajb Edi GdbjGe HMbGFb GdJMbjb hUdi Gddg Ydi eMeO NGJe GdfHjjf hYdi Bdg GdWjHjf GdWGgQjf hGdMeO ddg QH GdYGdejf s
(3HgG fXGe GdJYbjHIs
(3Ydjg hbas
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B78 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B173s
Keywords: (3GdCOHs